2018
DOI: 10.1039/c7ta08923f
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the opto-electronic and photoelectrochemical properties of FeVO4 photoanodes for solar water oxidation

Abstract: Molybdenum doping in FeVO4 photoanodes enhances the charge carrier mobility and lifetime, resulting in a 45% AM1.5 photocurrent increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(101 citation statements)
references
References 47 publications
10
91
0
Order By: Relevance
“…Signicant research efforts are therefore directed towards developing novel complex oxides with smaller bandgaps (1.7-1.9 eV) to replace BiVO 4 . [13][14][15][16][17][18] In addition, given the impressive development of solar water splitting devices, the next step is to shi beyond the laboratory experiments and demonstrate large-scale devices. Scaling can be quantied by the power of a device and can be increased by concentrating the solar irradiation or by increasing the photoabsorber area.…”
Section: Introductionmentioning
confidence: 99%
“…Signicant research efforts are therefore directed towards developing novel complex oxides with smaller bandgaps (1.7-1.9 eV) to replace BiVO 4 . [13][14][15][16][17][18] In addition, given the impressive development of solar water splitting devices, the next step is to shi beyond the laboratory experiments and demonstrate large-scale devices. Scaling can be quantied by the power of a device and can be increased by concentrating the solar irradiation or by increasing the photoabsorber area.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have reported the fabrication of FeVO 4 thin films using magnetron cosputtering, spray pyrolysis, dropcasting, and sol-gel methods with reported bandgap energy of 2.0-2.1 eV. [21][22][23][24][25][26][27][28][29][30][31] However, the achieved photocurrents are still very low as compared with the theoretical photocurrent based on the bandgap energy. We have previously identified that the main problem causing the low performance of FeVO 4 films is the poor bulk carrier separation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the materials are commonly hard and brittle. Moreover, they exhibit poor electronic conductivity due to the large bandgap (3)(4)(5). Conductive ceramic textiles that could be reversibly bent, polymer-like characteristic, would be extremely attractive for use in myriad engineering applications such as wearable electronics and energies.…”
Section: Introductionmentioning
confidence: 99%